SENTRALISASI PENGELOLAAN REKAM MEDIS DI PUSKESMAS BINAAN MIJEN KOTA SEMARANG DALAM MENYONGSONG SJSN DI INDONESIA - Retno Astuti S; Arif Kurniadi; Maryani Setyowati (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2014)
ABSTRACTResearch Program in Mijen Primary Health Center Semarang was based on a variety of problems found inthe field, which is related to the management of medical records that has not been stored in a centralized,thus does not guarantee the continuity of a patient’s medical information. While the continuity of medicalinformation be required to ensure the safety of medical services for the patients. Even the MRD storagesystems applied in inpatient filing system was not purely decentralized filing because a patient’s MRD storedper treatment period, not combined in 1 (one) inpatient MRD folder. In addition, storage management ofinactive and timeless MRD were not orderly. Inactive and timeless MRD are stacked in the warehouse withoutdocumentation and certain procedures.Solutions offered are medical records management training for 10 (ten) employees who worked at the TPPRJ,TPPRI, outpatient filing and inpatient filing of Mijen Primary Health Center. Furthermore, the design andsocialization of fixed procedures (SOPs) in the management of medical records TPPRJ, TPPRI, outpatient filingand inpatient filing, implementation of retention and inactive MRD value, as well as SOPs on implementation ofinactive and timeless MRD storage. In addition, the brief assistance in revamping medical record managementsystem in Mijen Primary Health Center.Research pogramme was carried out for 8 (eight) months. Subjects were interviewed and trained includes 1(one) Head of the Primary Health Center , 4 (four) outpatient filing personnel, 2 (two) inpatient filing personneland 6 (six) patients of Mijen Primary Health Center Semarang. The secondary data sources are outpatient,emergency and inpatient register, medical record management policies, SOP of medical records management,expedition books, as well as MRD borrowing card. Moreover, researchers have carried out observations ofactive medical records management system in outpatient and inpatient filing, inactive and timeless at MijenPrimary Health Center as a basis for preparing SOPs.Results of the devotion to be expected to solve problems in active medical record management system reformin Mijen Primary Health Center which are still established in decentralization to centralization. Anothermethod resulting is to fix the storage of family folder into 1 (one) folder for 1 (one) of a patient’s medical recordnumber. Furthermore, achieve medical record documents (MRD) alignment model which has been implementTerminal Digit Filing (TDF) with six (6) digit medical record number, but still based on 10 (ten) sub region.Thus, retrieval of medical data are expected to be achieved. In addition, result in the retention schedule andinactive and timeless MRD implementation method.Kata kunci: MRD, active, incative, timeless, registration place, filing, outpatient, inpatient